2016
DOI: 10.1080/09506608.2016.1204097
|View full text |Cite
|
Sign up to set email alerts
|

Spintronics technology: past, present and future

Abstract: Spintronics has emerged in the last two decades as both an extremely fruitful direction of research into the properties and usefulness of the spin degree of freedom of the electron as it can apply to the exponentially expanding world of electronics. Spintronics has infiltrated almost every household in the form of the read head sensors for the hard drives that inhabit every desktop and most laptop computers. Embedded magnetic random access memory (MRAM) and inplane STT-RAM are rapidly replacing SRAM in a host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 115 publications
0
46
0
4
Order By: Relevance
“…It has received great attention in the study of charge transport in heterostructures due to its application in spintronic devices [1][2][3]. Since the invention of diluted magnetic semiconductors (DMS) by Ohno many researchers have reported that spin polarization in semiconductor heterostructures can be achieved by using a ferromagmetic semiconductor material [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It has received great attention in the study of charge transport in heterostructures due to its application in spintronic devices [1][2][3]. Since the invention of diluted magnetic semiconductors (DMS) by Ohno many researchers have reported that spin polarization in semiconductor heterostructures can be achieved by using a ferromagmetic semiconductor material [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Nonmagnetic spacer materials sandwiched between ferromagnetic layers in hybrid multilayer nanostructures are of particular importance for enhancing the magnetoresistance, [2][3][4] controlling the resistance-area product (RA), [5][6][7] and even achieving interfacial perpendicular magnetic anisotropy (PMA). [8,9] Currently, the main spacer materials for magnetoresistance devices are MgO for magnetic tunnel junctions [2,3,8,9] and Cu or Ag for current-perpendicular-to-plane giant magnetoresistance (CPP-GMR) devices.…”
mentioning
confidence: 99%
“…A very small MR ratio was observed at room temperature of ~0.05%, and the MR increased to only ~0.07% at 50 K for the CFA/Cr/CFA structure. As introduced in Chapter 1, the output power of STNO would be proportional to (MR) 2 . Therefore, a small MR ratio will impede its application as a spin-torque oscillator.…”
Section: Discussionmentioning
confidence: 99%
“…By combining equation (2-3), (2-4), (2)(3)(4)(5) and (2)(3)(4)(5)(6), the TMR ratio can be written as:…”
Section: Tunneling Magnetoresistance (Tmr)mentioning
confidence: 99%
See 1 more Smart Citation